MAINSTREAMING WORKPLACE DIVERSITY AND INCLUSION (D&I): POTENTIAL ETHICAL IMPLICATIONS (CAHIERS MAGELLANES-NS, 2024)
Domestic and foreign companies of all sizes have pursued workplace diversity and inclusion for decades. Organizations succeed or fail based on society's ethics and diversity. Businesses recognize that society expects workplace tolerance and diversity. Fairness and inclusiveness in a business can enhance creativity, work happiness, and care quality, research shows. Workplace diversity boosts performance. Organizations can thrive with ethics and a code. Modern unethical firms are likely to fail. DEI underpins commercial ethics. Many companies support the policies yet emphasize DEI. A company's ethics code may promote diversity, equity, and inclusion. This study demonstrates the significance of diversity, equity, and inclusion (DEI) within the context of the workplace. The study provides insights into the motivations behind firms' adherence to workplace ethics and their commitment to diversity and inclusion. The significance of employee diversity and inclusion (D&I) and the ethical considerations for the future are of great importance to our organization.